EFFECTIVENESS ASSESSMENT OF THE ECONOMIC EMPOWERMENT PROGRAM (EEP): A CASE STUDY AMONG DISABLED TRAINERS AT CHESHIRE HOME SELANGOR - Subhi, Nasrudin (International Journal of Psychosocial Rehabilitation, 2020)
Disabled groups face many challenges when it comes to securing a job. Besides having to compete with the non-disabled candidates, access to oppurtunities and preparation are quite limited. Nevertheless, programs on special education and vocational studies have been actively initiated by many parties including the government bodies and private NGOs to help train disabled candidates. This study sets out to explore the effectiveness of an Economic Empowerment Program (EEP) carried out by an NGO called Cheshire Home situated in Selangor from the lens of (N= 14) alumni of this program via face-to-face focus group discussion. The three main objectives of this study is to (1) study the impact of EPP to disabled trainees on employability and personality, (2) explore experiences of the disabled trainees and (3) describe the understanding and perception of the disabled trainees at Cheshire Home Selangor towards EEP. The results revealed four main themes that emerged from the focus group discussion which were impact of EEP on trainees’ personality, employability, work experiences and challengers as well as trainees’ perception and understanding towards EEP.This study has generally illustrated EEP’s effectiveness that was carried out by Cheshire Home Selangor and has been seen to impact positively on the empowerment of disabled trainees.